Knowledge about cervical cancer in young Portuguese women: a cross-sectional study - Inês Oliveira Rodrigues; Inês Duarte; Carolina Gomes Costa; Ana Luís Pimentel; Sílvia Chaves; Ana Patrícia Gomes; Lina Santos; Joana Isabel Santos; Ana Cristina Moreira; Andrea Lobão; Isabel Nazaré; Paulo Santos; et al. (Frontiers in Public Health, 2024)
IntroductionHealth literacy is crucial to adherence to medical interventions in therapeutics, prevention, and diagnosis. The basis for literacy is knowledge. To accomplish the goals for the elimination of cervical cancer, one of the most prevalent and preventable cancers, we must understand the determinants of non-adherence and address them specifically to ensure patients’ active participation.AimTo determine women’s knowledge regarding the manifestations of cervical cancer and its prevention.Materials and methodsWe conducted a cross-sectional study in an urban population from northern Portugal. Women aged 18 to 30 years were randomly assigned to answer the Cervical Cancer Awareness Measure questionnaire, including questions of knowledge about the causes and symptoms of cervical cancer, prospecting for individual and social-related determinants.ResultsThe total number of participants was 270, with a mean age of 24.7 years. Knowledge about symptoms scored 5.4 ± 2.6, with a maximum of 12 points, and knowledge about the causes scored 5.7 ± 1.9, with a maximum of 11 points. The correlation between both was 0.334. High education, high socio-economic status, self-perception of one’s capacity to recognize symptoms, and knowledge about the HPV vaccine were associated with better knowledge.DiscussionPortuguese women present low knowledge about cervical cancer, potentially affecting their health through exposure to risk situations and non-adherence to routine screening.